Recreational Technologies (Elements of Floorball Sports) for Children of 5 and 6 Years of Age - Yurii Liannoi; Mykhailo Liannoi; Liudmyla Maksymenko; Yana Kopytina (Jan Długosz University in Częstochowa, 2019)
The article focuses on the reorganization of teaching and educational space, which would be based on the principles of innovation, and its integration into European and world educational space. It is ascertained that one of the priority methods for developing national education is to expand additional free opportunities for physical culture and sports classes in the system of educational institutions; to develop a network of free institutions of physical culture and sports for children and young people outside the system of formal education. The efficiency of recreational technologies in the teaching and educational process in educational institutions which improve the quality of sports and recreational activities and ensure their availability and performance has been proved. It is shown that using elements of floorball sports in the physical education preschool system improves the performance of physical development, physical fitness and psycho-emotional sphere of children of 5 and 6 years of age.